Process for the preparation of uiO-66-tix / tPIM-1 mixed matrix membranes for hexane isomer separation
Patent Information
- Application Number
- CN202611178857.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-30
AI Technical Summary
首先,该工艺必须严格控制微量氧参与反应,不仅增加了制备过程的操作复杂性,而且这种依赖氧气诱导的热交联机制会导致聚合物链段发生极为剧烈的致密化收缩,极易引发本征微孔的大规模塌陷,在分离液态烃时会导致膜的渗透通量发生断崖式下降;其次,该方案依然未能解决常规无机填料孔窗固定从而无法对己烷异构体进行精准甄别的问题
首先,本发明通过在合成过程中引入钛源,对UiO-66的局部配位环境进行精细调控,使其微孔孔窗产生适度收缩。该刚性微孔能够精准识别直链正己烷与高度支化异构体之间极微小的动力学直径差异,有效拦截支化分子,解决了常规无机填料孔窗固定、筛分精度不足的问题。
Smart Images

Figure CN122999000A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of membrane separation materials and liquid organic hydrocarbon separation technology, specifically relating to a UiO-66-Ti membrane for the separation of hexane isomers. x Preparation method of / tPIM-1 hybrid matrix membrane. Background Technology
[0002] Hexane isomer separation is a key process in petroleum refining and the high-value utilization of light naphtha. C6 alkane isomers include n-hexane, 2-methylpentane, 3-methylpentane, 2,3-dimethylbutane, and 2,2-dimethylbutane. Different isomers have significantly different octane numbers and downstream utilization values. Among them, n-hexane has a low octane number and can be used as an important chemical feedstock; while highly branched isomers have higher octane numbers and are important components in gasoline blending. Therefore, achieving accurate separation of C6 isomers is of great significance for improving naphtha component utilization efficiency and promoting molecular-level management in the refining process.
[0003] However, hexane isomers have similar boiling points and physicochemical properties, making them difficult to distinguish efficiently in traditional distillation processes, which typically require high energy consumption. While adsorption separation can achieve a degree of selective separation by utilizing differences in molecular size and configuration, it often suffers from high energy consumption for adsorbent regeneration, complex operation processes, and insufficient stability during continuous operation. Therefore, developing low-energy-consumption, high-selectivity, and continuously operable membrane separation technologies is an important direction for achieving efficient separation of hexane isomers. Pervaporation membrane separation technology relies on the chemical potential difference across the membrane to drive selective permeation of components, offering advantages such as low energy consumption, mild operating conditions, and ease of continuous operation. Mixed matrix membranes, by introducing porous inorganic or organic fillers into a polymer matrix, can simultaneously combine the good processability of polymers with the molecular sieving properties of porous fillers. Among them, PIM-1, due to its rigid, twisted main-chain structure and abundant intrinsic micropore free volume, exhibits high hydrocarbon molecule permeability, making it an ideal matrix material for constructing liquid hydrocarbon separation membranes.
[0004] Metal-organic frameworks (MOFs) possess regularly tunable pore sizes, window structures, and pore chemical environments, making them important functional fillers for constructing high-performance hybrid matrix membranes. UiO-66 exhibits excellent chemical stability, thermal stability, and a well-defined microporous structure, making it a potential candidate for hydrocarbon molecular sieving. Existing technology (Inorganic Chemistry, 2024, 63(28): 13031-13038) discloses a conventional UiO-66 / PIM-1 hybrid matrix membrane for hexane isomer separation. While this approach introduces conventional UiO-66 into a polymer matrix to improve separation performance, it still has significant limitations when dealing with complex liquid hydrocarbon systems. Due to the minimal differences in kinetic diameters among different hexane isomers, the pore window environment of the conventional UiO-66 used in this literature is relatively fixed, resulting in insufficient sieving accuracy for hexane isomers with small size differences and similar configurations, making it difficult to fully distinguish the subtle size and configuration differences between straight-chain n-hexane and branched hexane isomers. On the other hand, high-throughput polymer-based membranes such as PIM-1 are highly susceptible to solvation in liquid hydrocarbon systems, resulting in excessive volume expansion and severe chain segment relaxation. This not only leads to an increase in the intrinsic micropore size of the polymer and loss of selectivity, but also causes loosening and peeling of the interface between the polymer matrix and the inorganic filler, forming non-selective defect channels inside the membrane, resulting in a sharp deterioration in overall separation performance.
[0005] To address the stability issues of polymers in liquid environments, patent document WO2015129925A1 proposes a method for thermally oxidatively crosslinking PIM-1 through high-temperature heat treatment under controlled trace oxygen concentrations, and broadly suggests its application in mixed matrix membranes containing conventional metal-organic frameworks. While this approach effectively improves the polymer's anti-swelling properties through thermally oxidative crosslinking, it still faces serious drawbacks when dealing with the highly demanding separation of liquid hexane isomers. First, the process requires strict control of trace oxygen participation, which not only increases the operational complexity of the preparation process but also leads to extremely drastic densification and shrinkage of polymer segments due to this oxygen-dependent thermal crosslinking mechanism. This can easily cause large-scale collapse of intrinsic micropores, resulting in a precipitous drop in membrane permeation flux when separating liquid hydrocarbons. Second, this approach still fails to address the problem of fixed pore windows in conventional inorganic packings, which prevents accurate identification of hexane isomers. In existing hybrid matrix membrane systems, if there is a lack of effective synergy and size matching between the filler pore environment and the polymer thermal crosslinking network, it is easy to fall into a development bottleneck where flux and selectivity are mutually constrained.
[0006] Therefore, there is an urgent need to design and construct a novel mixed matrix membrane, which can simultaneously overcome the matrix volume expansion effect caused by liquid hexane, realize the matching of size and mass transfer between the continuous free volume of the polymer and the rigid micropores of the metal-organic framework filler, so as to construct a mass transfer path inside the membrane that combines polymer matrix-mediated adsorption transport and inorganic filler precision diffusion sieving, and finally achieve a two-way breakthrough in permeation flux and separation selectivity in hexane isomer separation. Contents of the Invention
[0007] In view of the above problems, the present invention performs titanium regulation on the pore windows of UiO-66 and heat treatment crosslinking on the mixed matrix membrane, and utilizes the preferential adsorption / dissolution effect of the heat-treated tPIM-1 matrix on n-hexane and the titanium-regulated UiO-66-Ti x diffusion restriction effect of the particles on branched hexane isomers, to construct a mass transfer path combining polymer matrix-mediated adsorption transport and MOF filler-mediated diffusion sieving, so as to realize the pervaporation separation of a mixture of n-hexane and branched hexane isomers.
[0008] To achieve the above objectives, the present invention adopts the following technical solutions: First, the present invention provides a preparation method of a UiO-66-Ti for hexane isomer separation x / tPIM-1 mixed matrix membrane, which comprises the following steps: (1) preparing a precursor mixed solution containing a zirconium source, a titanium source, an organic ligand and a solvent, and carrying out a reaction to prepare UiO-66-Ti x particles; wherein, the UiO-66-Ti x particles are bimetallic particles containing Zr and Ti, x is the ratio of the molar amount of Ti to the total molar amount of Zr and Ti, satisfying: 0<x ≤ 0.2, preferably 0.1≤x ≤ 0.2, more preferably x=0.2; (2) dissolving polymer PIM-1 in an organic solvent to form a PIM-1 casting solution; (3) adding the UiO-66-Ti obtained in step (1) x particles into the PIM-1 casting solution obtained in step (2), mixing uniformly to form a membrane, and performing solvent evaporation and drying to obtain a UiO-66-Ti x / PIM-1 mixed matrix membrane; (4) subjecting the UiO-66-Ti obtained in step (3) x / PIM-1 mixed matrix membrane to heat treatment under an inert atmosphere to obtain the titanium-regulated UiO-66-Ti x / tPIM-1 mixed matrix membrane.
[0009] As a preferred embodiment, in step (1), the precursor mixture further includes a regulator; the regulator is selected from one or more of acetic acid and formic acid; the zirconium source is selected from one or more of zirconium chloride, zirconium nitrate and zirconium oxychloride; the titanium source is selected from one or more of isopropyl titanate, tetrabutyl titanate and titanium tetrachloride; the organic ligand is terephthalic acid; and the solvent is N,N-dimethylformamide.
[0010] As a preferred embodiment, in step (1), the molar ratio of the zirconium source, titanium source, organic ligand, regulator and solvent is 0.8-1 : 0-0.2 : 1-3 : 50-150 : 100-600; the reaction is a solvothermal reaction with a reaction temperature of 80-120℃ and a reaction time of 12-24h.
[0011] As a preferred embodiment, in step (2), the organic solvent is selected from one or more of chloroform, dichloromethane, tetrahydrofuran, and N,N-dimethylformamide.
[0012] As a preferred embodiment, in step (3), the UiO-66-Ti x The particles in UiO-66-Ti x The mass fraction of the PIM-1 hybrid matrix membrane is 2.5% to 10%.
[0013] As a preferred embodiment, in step (3), the casting substrate is one of a glass plate, a glass dish, a polytetrafluoroethylene plate, or other inert flat substrate; the solvent evaporation process is carried out under closed or semi-closed conditions to obtain a dense self-supporting mixed matrix film.
[0014] As a preferred embodiment, in step (4), the inert atmosphere is selected from nitrogen and argon or a combination thereof; the temperature of the heat treatment is 360~400℃, and the time of the heat treatment is 1~24h, more preferably 12~24h.
[0015] The present invention also provides a UiO-66-Ti for the separation of hexane isomers. x / tPIM-1 hybrid matrix membrane, which is prepared by the above preparation method; The hybrid matrix membrane comprises a tPIM-1 polymer matrix and UiO-66-Ti dispersed in the tPIM-1 polymer matrix. x Particles; wherein the tPIM-1 polymer matrix is a matrix formed by crosslinking polymer PIM-1 after heat treatment under an inert atmosphere.
[0016] Finally, the present invention also provides the above-mentioned UiO-66-Ti x Application of / tPIM-1 hybrid matrix membrane in pervaporation separation of liquid hexane isomers.
[0017] As a preferred embodiment, the hexane isomer is a mixture comprising straight-chain n-hexane and branched hexane isomers; the branched hexane isomer is selected from one or more of 2-methylpentane, 3-methylpentane, 2,3-dimethylbutane and 2,2-dimethylbutane.
[0018] As a preferred embodiment, the operating temperature of the pervaporation separation is 20~80℃; the operating feed mass ratio of straight-chain n-hexane to branched hexane isomers in the mixture is 10:90~90:10.
[0019] Compared with the prior art, the present invention has the following beneficial effects: First, this invention introduces a titanium source during the synthesis process to precisely control the local coordination environment of UiO-66, causing its micropores to shrink appropriately. These rigid micropores can accurately identify the minute differences in kinetic diameter between straight-chain n-hexane and highly branched isomers, effectively intercepting branched molecules and solving the problems of fixed pore windows and insufficient sieving accuracy in conventional inorganic packings.
[0020] Secondly, this invention involves performing overall heat treatment on the molded mixed matrix membrane under a completely inert atmosphere, causing the polymer to crosslink and transform into a stable tPIM-1 matrix. This process fundamentally overcomes the excessive volume expansion and chain segment relaxation that commonly occur in conventional polymer membranes in liquid organic hydrocarbons, and completely eliminates the non-selective defects caused by interfacial peeling.
[0021] Finally, this invention successfully constructed a mass transfer pathway that synergistically combines polymer adsorption transport with inorganic filler diffusion sieving. Although thermal crosslinking causes a certain degree of densification in the polymer matrix, the uniformly dispersed titanium-regulated inorganic particles provide unobstructed additional microporous transport regions for the preferentially permeating components, perfectly compensating for the mass transfer resistance of the matrix. The synergistic effect of these two factors enables this hybrid matrix membrane to achieve a significant bidirectional improvement in both permeation flux and separation selectivity in the complex separation of liquid hexane isomers. Attached Figure Description
[0022] Figure 1 UiO-66-Ti with different Ti doping amounts prepared for Examples 1-2 and Comparative Examples 1-4 x XRD patterns of particles; Figure 2 UiO-66-Ti with different Ti doping amounts prepared for Examples 1-2 and Comparative Examples 1-4 x Nitrogen adsorption-desorption isotherm curves (left) and pore size distribution (right) of particles at 77 K. Figure 3 UiO-66-Ti with different Ti doping amounts prepared for Examples 1-2 and Comparative Examples 1-4x FT-IR spectra of particles; Figure 4 UiO-66-Ti with different Ti doping amounts prepared for Examples 1-2 and Comparative Examples 1-4 x XPS full spectrum of the particle (top left), actual doping amount (bottom left), and oxygen fine spectrum (right). Figure 5 UiO-66-Ti prepared in Example 1 0.2 SEM images of the surface (left) and cross-section (right) of / tPIM-1; Figure 6 The UiO-66-Ti prepared in Examples 1-2 and Comparative Examples 1-4 x Comparison of the separation performance of / tPIM-1 for hexane isomers (equimolar feed of n-hexane: 22DMB-1:1); Figure 7 The heat-treated UiO-66-Ti prepared in Example 1 and Comparative Example 8 0.2 / PIM-1 and untreated UiO-66-Ti 0.2 Comparison of the separation performance of / tPIM-1 for hexane isomers (equimolar feed of n-hexane: 22DMB-1:1); Figure 8 The UiO-66-Ti with different MOF loadings prepared in Examples 1, 3, 4 and Comparative Examples 5-7 x Comparison of the separation performance of / tPIM-1 for hexane isomers (equimolar feed of n-hexane: 22DMB-1:1); Figure 9 The UiO-66-Ti prepared in Example 1 0.2 / tPIM-1 membrane separation performance under different feed ratios; Figure 10 The UiO-66-Ti prepared in Example 1 0.2 Separation performance of / tPIM-1 membrane under different hexane isomers in binary components; Figure 11 The UiO-66-Ti prepared in Example 1 0.2 / tPIM-1 membrane separation performance under five hexane isomers. Detailed Implementation
[0023] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings involved in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of the present invention, and not all embodiments. Any other embodiments obtained by those skilled in the art based on these drawings without creative effort are within the protection scope of the present invention.
[0024] Example 1 This embodiment provides a titanium-modulated UiO-66-Ti x The / tPIM-1 hybrid matrix membrane and its preparation method are detailed below: (1) Preparation of UiO-66-Ti with Ti doping content of 20% by in-situ solvothermal method 0.2 The particles were prepared by adding zirconium chloride and isopropyl titanate in a molar ratio of 0.8:0.2 (total molar amount fixed at 0.86 mmol) to 2 mL of N,N-dimethylformamide and sonicating for 10 min until a homogeneous and transparent metal precursor solution was formed. Then, 0.19 g of terephthalic acid and 3.61 mL of acetic acid were added to 13 mL of N,N-dimethylformamide and stirred until completely dissolved to obtain a homogeneous ligand solution. The metal precursor solution was slowly added to the ligand solution, and stirring was continued for 10 min to ensure thorough mixing. Finally, the resulting mixture was transferred to a stainless steel high-pressure reactor with a PTFE liner and reacted in a 100 °C electric heating oven for 24 h. After the reaction, the mixture was allowed to cool naturally to room temperature, and the product was collected by centrifugation. The product was then repeatedly washed with N,N-dimethylformamide and methanol to remove unreacted precursors and residual solvent in the pores, followed by vacuum drying to obtain UiO-66-Ti. 0.2 Particles.
[0025] (2) Preparation of PIM-1 polymer: 3.4 g of 5,5′,6,6′-tetrahydroxy-3,3,3′,3′-tetramethyl-1,1′-spiro-indole and 2.0 g of 2,3,5,6-tetrafluoroterephthalonitrile were added to a dry three-necked flask, along with 70 mL of anhydrous N,N-dimethylformamide. The mixture was heated to 65 °C under an argon atmosphere and stirred continuously until a homogeneous solution was formed. Then, 4.1 g of finely ground anhydrous potassium carbonate was gradually added, and the reaction was continued at 65 °C for 72 h. After the reaction was completed, the resulting reaction solution was slowly poured into 650 mL of deionized water to precipitate the polymer. The obtained solid was collected and repeatedly purified by dissolving in chloroform and precipitating with methanol. It was then washed successively with 1,4-dioxane, acetone, water, and excess methanol to remove residual monomers, inorganic salts, and low molecular weight impurities. Finally, the obtained bright yellow PIM-1 powder was dried overnight in a vacuum oven at 120 °C for later use.
[0026] (3) Preparation of UiO-66-Ti by solution casting method 0.2The PIM-1 mixed matrix membrane was prepared by adding 0.3 g of pre-vacuum-dried PIM-1 powder to 10 g of chloroform and stirring at room temperature until completely dissolved to obtain a homogeneous PIM-1 casting solution. Subsequently, 0.015 g of UiO-66-Ti was added to the casting solution. 0.2 The particles were then subjected to continuous stirring and ultrasonic treatment of the mixed suspension to promote the formation of UiO-66-Ti particles. 0.2 The particles were uniformly dispersed in the PIM-1 matrix. The casting solution was then allowed to stand to degas, poured into a clean glass dish, and the solvent was slowly evaporated under sealed conditions to form a dense, self-supporting mixed matrix film, yielding 5 wt.% UiO-66-Ti. 0.2 / PIM-1. The resulting film was further dried under vacuum to completely remove residual solvent. Simultaneously, the obtained UiO-66-Ti... 0.2 The PIM-1 hybrid matrix membrane was heat-treated under a nitrogen atmosphere at 370 ℃ for 12 h to obtain the heat-treated UiO-66-Ti. 0.2 / tPIM-1 hybrid matrix membrane.
[0027] Example 2 The only difference between this embodiment and Example 1 is that in step (1), zirconium chloride and isopropyl titanate are mixed in a molar ratio of 0.9:0.1 (total molar amount is fixed at 0.86 mmol) to prepare UiO-66-Ti. 0.1 / tPIM-1 hybrid matrix membrane.
[0028] Example 3 The only difference between this embodiment and Embodiment 1 is that 0.008 g of UiO-66-Ti is added to the casting solution in step (3). 0.2 Particles were prepared to obtain 2.5 wt.% UiO-66-Ti 0.2 / tPIM-1 hybrid matrix membrane.
[0029] Example 4 The only difference between this embodiment and Embodiment 1 is that 0.030 g of UiO-66-Ti is added to the casting solution in step (3). 0.2 Particles were prepared to obtain 10 wt.% UiO-66-Ti 0.2 / tPIM-1 hybrid matrix membrane.
[0030] Comparative Example 1 The only difference between this comparative example and Example 1 is that in step (1), zirconium chloride and isopropyl titanate are mixed in a molar ratio of 1.0:0 (total molar amount is fixed at 0.86 mmol) to prepare a UiO-66-Ti0 / tPIM-1 mixed matrix membrane.
[0031] Comparative Example 2 The only difference between this embodiment and Example 1 is that in step (1), zirconium chloride and isopropyl titanate are mixed in a molar ratio of 0.6:0.4 (total molar amount is fixed at 0.86 mmol) to prepare UiO-66-Ti. 0.4 / tPIM-1 hybrid matrix membrane.
[0032] Comparative Example 3 The only difference between this comparative example and Example 1 is that in step (1), zirconium chloride and isopropyl titanate are mixed in a molar ratio of 0.4:0.6 (total molar amount is fixed at 0.86 mmol) to prepare UiO-66-Ti. 0.6 / tPIM-1 hybrid matrix membrane.
[0033] Comparative Example 4 The only difference between this comparative example and Example 1 is that in step (1), zirconium chloride and isopropyl titanate are mixed in a molar ratio of 0.2:0.8 (total molar amount is fixed at 0.86 mmol) to prepare UiO-66-Ti. 0.8 / tPIM-1 hybrid matrix membrane.
[0034] Comparative Example 5 The only difference between this comparative example and Example 1 is that 0 g of UiO-66-Ti was added to the casting solution in step (3). 0.2 Particles were prepared to obtain 0 wt.% UiO-66-Ti 0.2 / tPIM-1 hybrid matrix membrane.
[0035] Comparative Example 6 The only difference between this comparative example and Example 1 is that 0.045 g of UiO-66-Ti was added to the casting solution in step (3). 0.2 Particles were prepared to obtain 15 wt.% UiO-66-Ti 0.2 / tPIM-1 hybrid matrix membrane.
[0036] Comparative Example 7 The only difference between this comparative example and Example 1 is that 0.06 g of UiO-66-Ti was added to the casting solution in step (3). 0.2 Particles were prepared to obtain 20 wt.% UiO-66-Ti 0.2 / tPIM-1 hybrid matrix membrane.
[0037] Comparative Example 8 The only difference between this comparative example and Example 1 is that the UiO-66-Ti obtained in step (3) 0.2 / PIM-1 hybrid matrix membranes do not undergo heat treatment.
[0038] Characterization results like Figure 1 As shown, the different Ti-doped UiO-66-TiO and UiO-66-TiO prepared in Examples 1-2 and Comparative Examples 1-4 were analyzed by XRD. 0.1 UiO-66-Ti 0.2 UiO-66-Ti 0.4 UiO-66-Ti 0.6 and UiO-66-Ti 0.8 The particles were characterized to investigate the effect of Ti introduction on the crystal structure of UiO-66. The results showed that UiO-66-Ti0 and UiO-66-Ti... 0.1 and UiO-66-Ti 0.2 All samples retained the characteristic diffraction peaks typical of UiO-66 crystals, indicating that low to medium Ti doping levels do not significantly disrupt the UiO-66 main framework structure. With further increases in Ti doping levels to 0.4, 0.6, and 0.8, UiO-66-Ti was obtained. 0.4 UiO-66-Ti 0.6 and UiO-66-Ti 0.8 The characteristic peaks of UiO-66 gradually weaken, indicating that the introduction of excessive Ti affects the nucleation and growth process of UiO-66 crystals and weakens its long-range ordered structure. In addition, the main diffraction peaks of UiO-66 gradually shift to higher angles with increasing Ti content, indicating that the introduction of Ti induces lattice shrinkage in UiO-66.
[0039] like Figure 2 As shown, the UiO-66-TiO and UiO-66-TiO prepared with different Ti doping amounts in Examples 1-2 and Comparative Examples 1-4 were further analyzed by nitrogen adsorption-desorption tests. 0.1 UiO-66-Ti 0.2 UiO-66-Ti 0.4 UiO-66-Ti 0.6 and UiO-66-Ti 0.8 Variations in the pore structure of the particles. UiO-66-Ti0, UiO-66-Ti 0.1 and UiO-66-Ti 0.2 The specific surface areas of BET were 1588, 1532 and 1399 m², respectively. 2 ·g -1 This indicates that the introduction of low Ti content only slightly reduces the accessible microporous structure of the material, while still maintaining the microporous characteristics of the UiO-66 framework. In contrast, UiO-66-Ti 0.4 UiO-66-Ti 0.6and UiO-66-Ti 0.8 The specific surface areas of BET decreased to 842, 485 and 374 m², respectively. 2 ·g -1 This indicates that high Ti content significantly reduces the crystallinity and microporous order of the material. Pore size distribution results show that the micropore size of UiO-66-TiO is approximately 0.63 nm, while that of UiO-66-TiO... 0.2 The micropore diameter is approximately 0.61 nm, indicating that the introduction of an appropriate amount of Ti can cause a slight shrinkage of the UiO-66 pore window, thus providing a more favorable size sieving basis for the subsequent separation of n-hexane / 2,2-dimethylbutane.
[0040] like Figure 3 As shown, FTIR was used to further verify the different Ti-doped UiO-66-TiO and UiO-66-TiO prepared in Examples 1-2 and Comparative Examples 1-4. 0.1 UiO-66-Ti 0.2 UiO-66-Ti 0.4 UiO-66-Ti 0.6 and UiO-66-Ti 0.8 Changes in the chemical structure of the particles. With increasing Ti doping content, the 657 cm⁻¹... -1 The Zr-O vibration peaks near the 416 cm⁻¹ gradually weaken, while those at 416 cm⁻¹... -1 The vibrational peaks associated with Ti-O in the vicinity gradually increased, indicating that Ti species were successfully introduced into the UiO-66 framework or its local coordination environment.
[0041] like Figure 4 As shown, XPS further confirmed the presence of Ti in UiO-66-TiO and UiO-66-Ti prepared with different Ti doping amounts in Examples 1-2 and Comparative Examples 1-4. 0.1 UiO-66-Ti 0.2 UiO-66-Ti 0.4 UiO-66-Ti 0.6 and UiO-66-Ti 0.8Successful introduction of Ti into the particles and its regulatory effect on the local chemical environment. XPS full-spectrum results showed that as the Ti doping amount gradually increased from 0 to 0.8, the Ti element signal in the sample gradually increased, while the Zr element signal correspondingly decreased, indicating that Ti species were effectively introduced into the UiO-66 system. Quantitative analysis of the Ti and Zr element contents showed that the actual Ti content gradually increased with the increase of the nominal Ti doping amount, indicating that the preparation method can achieve controllable adjustment of the Ti content in UiO-66. Further analysis of the O 1s high-resolution XPS spectrum revealed that the UiO-66-Ti0 sample without Ti introduction was mainly composed of CO and Zr-O related oxygen species; as the Ti doping amount increased, components related to Ti-O bonds gradually appeared and strengthened in the O 1s spectrum, indicating that Ti species were not simply physically adsorbed on the particle surface, but participated in the construction of the local coordination environment of the UiO-66 metal-oxygen clusters. Meanwhile, obvious Ti characteristic peaks can be observed in the Ti 2p high-resolution spectrum, and their intensity increases with the increase of Ti doping amount; while the Zr-related signal in the Zr3d spectrum shows a relatively weakening trend, further proving that Ti species gradually participate in the regulation process of Zr-based metal cluster environment.
[0042] like Figure 5 As shown, the UiO-66-Ti prepared in Example 1 under nitrogen heat treatment at 370 °C x / tPIM-1 hybrid matrix membranes were obtained, and their surface and cross-sectional morphology were observed by SEM. The results show that all obtained hybrid matrix membranes are continuous self-supporting membranes, UiO-66-Ti 0.2 The particles can be dispersed in the tPIM-1 matrix to form a dense hybrid matrix membrane structure.
[0043] like Figure 6 As shown, the effect of Ti doping amount on the separation performance of the mixed matrix membrane was evaluated under normal pressure and 25 °C. o Under C conditions, using a binary mixture of n-hexane / 2,2-dimethylbutane in an equal mass ratio as the feed system, different UiO-66-Ti alloys prepared in Examples 1-2 and Comparative Examples 1-4 were tested. x Pervaporation separation tests were conducted on the UiO-66-Ti0 / tPIM-1 membrane. With increasing Ti doping concentration, the total membrane flux gradually increased, while the separation factor showed a trend of first increasing and then decreasing. Specifically, the separation factor changed from UiO-66-Ti0 / tPIM-1 membrane to UiO-66-Ti0 / tPIM-1 membrane. 0.2 / tPIM-1 membrane, total flux increased from 0.424 kg·m -2 h -1 Increased to 0.483 kg·m -2 h -1The separation factor for n-hexane / 2,2-dimethylbutane increased from 3.64 to 7.94, indicating that the introduction of an appropriate amount of Ti can enhance the molecular sieving ability of the membrane while improving mass transfer efficiency. This performance improvement is mainly attributed to UiO-66-Ti. 0.2 It maintained a good crystal structure, and its moderately contracted pore window environment enhanced its ability to distinguish the size of straight-chain n-hexane and highly branched 2,2-dimethylbutane. When the Ti doping amount was further increased to 0.8, the total membrane flux increased to 1.731 kg·m. -2 h -1 However, the separation factor dropped to 1.01, indicating that the introduction of excessive Ti led to a decrease in the crystallinity of UiO-66 filler, a weakening of the microporous structure, and the generation of non-selective transport paths, thereby severely weakening the molecular sieving ability of the membrane.
[0044] like Figure 7 As shown, the effect of heat treatment on the separation performance of hexane isomers was evaluated using a Ti-doped mixed matrix membrane, with UiO-66-Ti as an example. 0.2 As a filler, a mixed matrix membrane was prepared and subjected to atmospheric pressure and 25°C. o Under C conditions, using a binary mixture of n-hexane / 2,2-dimethylbutane in an equal mass ratio as the feed system, the separation performance of nHex / 22DMB before and after heat treatment was compared. The results showed that the untreated PIM-1 / UiO-66-Ti 0.2 The membrane (Comparative Example 8) exhibited a high permeation flux of 0.883 kg·m. -2 ·h -1 However, its separation factor was only 2.32, indicating that the membrane exhibits a certain degree of segmental swelling or non-selective mass transfer channels in the liquid hydrocarbon system. After heat treatment, tPIM-1 / UiO-66-Ti 0.2 The flux of the membrane (Example 1) was reduced to 0.515 kg·m. -2 ·h -1 However, the separation factor significantly increased to 7.94. This result indicates that heat treatment can effectively stabilize the PIM-1 polymer matrix, suppress liquid hydrocarbon-induced segmental swelling and non-selective permeation, thereby enhancing the performance of UiO-66-Ti. 0.2 The selective mass transfer channels constructed by the packing material and the polymer matrix improve the separation selectivity of nHex / 22DMB.
[0045] like Figure 8 As shown, the different UiO-66-Ti prepared in Examples 1, 3, 4 and Comparative Examples 5-7 were further examined. 0.2 The effect of filler content on the structure and separation performance of mixed matrix membranes. At atmospheric pressure and 25°C... oUnder C conditions, pervaporation separation tests were conducted using a binary mixture of n-hexane and 2,2-dimethylbutane in an equal mass ratio as the feed system. With UiO-66-Ti 0.2 As the filler content increased from 0 to 5 wt.%, the total membrane flux increased from 0.424 kg·m³. -2 h -1 Increased to 0.515 kg·m -2 h -1 The separation factor for n-hexane / 2,2-dimethylbutane increased from 3.64 to 7.94, indicating that an appropriate amount of UiO-66-Ti... 0.2 The introduction of filler material can simultaneously improve the membrane's mass transfer efficiency and molecular sieving ability. On the one hand, UiO-66-Ti 0.2 The particles provide additional microporous transport regions within the membrane, which is beneficial for increasing the permeate flux of n-hexane. On the other hand, the Ti-regulated UiO-66 pore window environment provides stronger diffusion restriction for highly branched 2,2-dimethylbutane, thereby improving the separation factor. When the packing content is further increased to 20 wt.%, the total membrane flux increases to 1.331 kg·m³. -2 h -1 However, the separation factor decreased to 1.04. This indicates that under high filler content, UiO-66-Ti... 0.2 The particles tend to aggregate significantly, forming interfacial defects or non-selective transport channels at the polymer / filler interface. This leads to easier co-permeation of 2,2-dimethylbutane with n-hexane, thereby weakening the membrane's separation selectivity. Therefore, 5 wt.% was determined to be UiO-66-Ti. 0.2 The preferred filler content of the / tPIM-1 hybrid matrix membrane is one that achieves a better balance between filler functionalization and membrane structural integrity.
[0046] like Figure 9 As shown, this is to evaluate the UiO-66-Ti prepared in Example 1. 0.2 The adaptability of the / tPIM-1 mixed matrix membrane under different feed compositions was tested using mixtures with different hexane / 2,2-dimethylbutane mass ratios (1:9, 3:7, 5:5, 7:3, 9:1) at atmospheric pressure and 25°C. o Under condition C, pervaporation separation tests were conducted. When the hexane content in the feed increased from 10 wt.% to 90 wt.%, the total membrane flux increased from 0.194 kg·m⁻¹. -2 h -1 Increased to 0.815 kg·m -2 h -1This change indicates that as the proportion of the preferentially permeating component, n-hexane, in the feed increases, the contribution of n-hexane transport within the membrane strengthens, thus gradually increasing the total flux. Simultaneously, the separation factor does not change monotonically with the n-hexane content, but reaches its highest value of 7.94 when the mass ratio of n-hexane to 2,2-dimethylbutane is 5:5, indicating the existence of certain component competition and coupled mass transfer behavior in the mixed feed system. Under equal mass feed conditions, the preferential adsorption / transport of n-hexane and the diffusion restriction of 2,2-dimethylbutane achieve a good balance, thus exhibiting the highest separation factor. These results demonstrate the effectiveness of the prepared UiO-66-Ti membrane. 0.2 The / tPIM-1 hybrid matrix membrane can maintain effective separation capability of n-hexane / 2,2-dimethylbutane over a wide range of feed compositions, and has the potential to adapt to fluctuations in the composition of complex hydrocarbon feeds.
[0047] like Figure 10 As shown, further at normal pressure, 25 o Under condition C, the UiO-66-Ti prepared in Example 1 was tested. 0.2 The / tPIM-1 mixed matrix membrane demonstrates strong separation capabilities for binary systems of different C6 isomers at equal mass ratios. Results show that the membrane's separation factors for the hexane / 2-methylpentane and hexane / 3-methylpentane systems are 3.43 and 3.25, respectively; while the separation factors for the hexane / 2,3-dimethylbutane and hexane / 2,2-dimethylbutane systems are increased to 7.36 and 7.94, respectively. Given that the kinetic diameters of 2-methylpentane and 3-methylpentane are approximately 5.0 Å, while those of 2,3-dimethylbutane and 2,2-dimethylbutane are approximately 5.8 Å and 6.2 Å, respectively, this indicates that the mixed matrix membrane exhibits stronger diffusion confinement for highly branched, larger C6 isomers, making it more suitable for separating straight-chain hexane from highly branched isomers.
[0048] like Figure 11 As shown, to further verify its application potential in complex systems, an equimolar mixture of five C6 isomers consisting of n-hexane (nHex), 2-methylpentane (2MP), 3-methylpentane (3MP), 2,3-dimethylbutane (23DMB), and 2,2-dimethylbutane (22DMB) was used as a model feed. The mixture was subjected to atmospheric pressure and 25... o Pervaporation tests were conducted under C conditions. The results showed that n-hexane was preferentially enriched on the permeate side to approximately 58.9%, indicating that the membrane can still preferentially transport straight-chain n-hexane even in a multi-component competitive mass transfer environment. In contrast, the content of branched isomers on the permeate side was significantly reduced, especially the dibranched isomers such as 2,3-dimethylbutane and 2,2-dimethylbutane, which were more significantly suppressed. These results demonstrate that UiO-66-Ti 0.2The / tPIM-1 hybrid matrix membrane is suitable not only for the separation of binary C6 isomers, but also for the selective enrichment and separation of multi-component light naphtha-related C6 isomer systems. UiO-66-Ti 0.2 / tPIM-1 hybrid matrix membrane can effectively distinguish between low-octane straight-chain components and high-octane branched components in complex hydrocarbon mixtures, providing a promising membrane separation material for molecular-level refining of light naphtha, removal of straight-chain alkanes, and enrichment of high-octane components.
[0049] The technical solution of the present invention has been described in detail above with reference to the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to help those skilled in the art better understand the core idea of the present invention, and are not intended to be an absolute limitation on the scope of protection of the present invention. For those skilled in the art, various local modifications, equivalent substitutions, or combinations can be made to the above-described specific embodiments (e.g., fine-tuning the type of metal source, specific polymerization or thermal crosslinking parameters, and specific pervaporation operating conditions, etc.) without departing from the concept and physicochemical mechanism of the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be covered within the patent protection scope defined by the claims of this application.
Claims
1. A UiO-66-Ti for the separation of hexane isomers x The method for preparing / tPIM-1 hybrid matrix membrane is characterized by, comprising the following steps: (1) preparing a precursor mixed solution containing a zirconium source, a titanium source, an organic ligand and a solvent, and reacting to obtain UiO-66-Ti x particles; wherein the UiO-66-Ti x particles are bimetallic particles containing Zr and Ti, x is the ratio of the molar amount of Ti to the total molar amount of Zr and Ti, satisfying: 0<x ≤ 0.2; (2) dissolving polymer PIM-1 in an organic solvent to form a PIM-1 casting solution; (3) adding the UiO-66-Ti obtained in step (1) x particles into the PIM-1 casting solution obtained in step (2), mixing uniformly to form a membrane, volatilizing the solvent and drying to obtain UiO-66-Ti x / PIM-1 mixed matrix membrane; (4) subjecting the UiO-66-Ti obtained in step (3) x / PIM-1 mixed matrix membrane to heat treatment under an inert atmosphere to obtain the titanium-regulated UiO-66-Ti x / tPIM-1 mixed matrix membrane.
2. The method according to claim 1, characterized in that, In step (1), the precursor mixture further includes a regulator; the regulator is selected from one or more of acetic acid and formic acid; the zirconium source is selected from one or more of zirconium chloride, zirconium nitrate and zirconium oxychloride; the titanium source is selected from one or more of isopropyl titanate, tetrabutyl titanate and titanium tetrachloride; the organic ligand is terephthalic acid; and the solvent is N,N-dimethylformamide.
3. The method according to claim 2, characterized in that, In step (1), the molar ratio of the zirconium source, titanium source, organic ligand, regulator and solvent is 0.8-1 : 0-0.2 : 1-3 : 50-150 : 100-600; the reaction is a solvothermal reaction with a reaction temperature of 80-120℃ and a reaction time of 12-24h.
4. The method according to claim 1, characterized in that, In step (2), the organic solvent is selected from one or more of chloroform, dichloromethane, tetrahydrofuran and N,N-dimethylformamide.
5. The method according to claim 1, characterized in that, In step (3), the UiO-66-Ti x The particles in the UiO-66-Ti x The mass fraction of the PIM-1 hybrid matrix membrane is 2.5% to 10%.
6. The method according to claim 1, characterized in that, In step (4), the inert atmosphere is selected from nitrogen and argon or a combination thereof; the temperature of the heat treatment is 360~400℃, and the time of the heat treatment is 1~24h.
7. A UiO-66-Ti for the separation of hexane isomers x / tPIM-1 hybrid matrix membrane, characterized in that, The hybrid matrix membrane is prepared by the preparation method according to any one of claims 1 to 6; the hybrid matrix membrane comprises a tPIM-1 polymer matrix and UiO-66-Ti dispersed in the tPIM-1 polymer matrix. x Particles; wherein the tPIM-1 polymer matrix is a matrix formed by crosslinking polymer PIM-1 after heat treatment under an inert atmosphere.
8. A UiO-66-Ti as described in claim 6 or 7 x Application of / tPIM-1 hybrid matrix membrane in pervaporation separation of liquid hexane isomers.
9. The application according to claim 8, characterized in that, The hexane isomer is a mixture comprising straight-chain n-hexane and branched hexane isomers; the branched hexane isomer is selected from one or more of 2-methylpentane, 3-methylpentane, 2,3-dimethylbutane and 2,2-dimethylbutane.
10. The application according to claim 9, characterized in that, The operating temperature for the pervaporation separation is 20~80℃; the feed mass ratio of straight-chain n-hexane to branched hexane isomers in the mixture is 10:90~90:10.
Citation Information
Patent Citations
Crosslinked polymer, method for producing the same, molecular sieve composition and material separation membranes
WO2015129925A1
